2012
DOI: 10.3389/fnmol.2011.00062
|View full text |Cite
|
Sign up to set email alerts
|

gp130 cytokines are positive signals triggering changes in gene expression and axon outgrowth in peripheral neurons following injury

Abstract: Adult peripheral neurons, in contrast to adult central neurons, are capable of regeneration after axonal damage. Much attention has focused on the changes that accompany this regeneration in two places, the distal nerve segment (where phagocytosis of axonal debris, changes in the surface properties of Schwann cells, and induction of growth factors and cytokines occur) and the neuronal cell body (where dramatic changes in cell morphology and gene expression occur). The changes in the axotomized cell body are of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
66
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 252 publications
(365 reference statements)
1
66
0
Order By: Relevance
“…Together with other glycoprotein-130-related cytokines, LIF activates the Janus kinase and STAT pathways (48). The capacity of LIF to counteract oxidative stress (29,51) fits well with the described role of transferrin in the retina, and as our study found both proteins at reduced levels in de-differentiated cells concomitant with a loss of survival-prolonging capacities, this suggests an important role of RMGs in buffering oxidative stress in the healthy retina.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Together with other glycoprotein-130-related cytokines, LIF activates the Janus kinase and STAT pathways (48). The capacity of LIF to counteract oxidative stress (29,51) fits well with the described role of transferrin in the retina, and as our study found both proteins at reduced levels in de-differentiated cells concomitant with a loss of survival-prolonging capacities, this suggests an important role of RMGs in buffering oxidative stress in the healthy retina.…”
Section: Discussionsupporting
confidence: 62%
“…LIF belongs to the IL6 family, also termed glycoprotein 130 cytokines (48). Other members of this cytokine family include ciliary neurotrophic factor, IL11, and oncostatin M, all of which signal through a common glycoprotein 130 receptor (48). LIF exhibits multiple biological effects in the developing vertebrate retina (49) and has been widely investigated as a neurotrophic factor in the retina (14, 50 -52).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the brain, LIF is involved in neural stem cell maintenance and axonal growth, and in modulation of gene expression [100]. During embryonic development, LIF is expressed in the olfactory placode, which led to the hypothesis that LIF affects GnRH neuron migration [54].…”
Section: Discussionmentioning
confidence: 99%
“…They are subgrouped into peptide families according to sequence similarity and homology of receptors to which they bind. Several comprehensive reviews have described the localization, regulation, and function of neurotrophins (NGF, BDNF, NT-3/4/5), glial cellderived neurotrophic factor (GDNF) family members (GDNF, NTN, PSP, ART), fibroblast growth factors (FGF-1, FGF-2), insulin-like growth factors (IGF-I, IGF-II), neuregulins (GGF), neuropeptides (galanin, VIP, PACAP), and neuropoietic cytokines belonging to the gp130 family (CNTF, LIF, CT-1, OSM, IL-6, IL-11) in the lesioned peripheral nervous system (PNS) (Boyd & Gordon, 2003;Fawcett & Keynes, 1990;Fu & Gordon, 1997;Gordon, 2009;Grothe, Haastert, & Jungnickel, 2006;Hökfelt, Zhang, & Wiesenfeld-Hallin, 1994;Klimaschewski, Kummer, & Heym, 1996;Terenghi, 1999;Zigmond, 2012). Here, we focus our discussion on the ability of these molecules to promote neuronal survival and regeneration in the lesioned PNS, with particular emphasis on their role in axonal sprouting.…”
Section: Polypeptide Families Involved In Peripheral Axon Regenerationmentioning
confidence: 99%